A 90 day oral toxicity study of blueberry polyphenols in ovariectomized sprague-dawley rats. (May 2020) - Cladis, Dennis P.; Li, Shiyu; Reddivari, Lavanya; Cox, Abigail; Ferruzzi, Mario G.; Weaver, Connie M.
Abstract: Regular consumption of polyphenol-rich fruits and vegetables is associated with beneficial health outcomes. To increase polyphenol intakes, consumers are increasingly using herbal and botanical dietary supplements containing concentrated polyphenol extracts. However, the safety of this consumption modality has not been vetted. To address this, ovariectomized Sprague-Dawley (OVX-SD) rats were orally gavaged with purified blueberry polyphenols at 0–1000 mg total polyphenols/kg bw/d for 90d. No differences in behavior, body weight, or food consumption were observed. No tumors or macroscopic changes were observed, and histopathological analyses showed no differences among groups. Although several statistically significant differences between treatment and control groups were observed in urine (color and pH) and blood (monocyte count, total cholesterol, and chloride ion concentration) analyses, these parameters were within normal ranges and not considered biologically significant. Intestinal permeability assessed via FITC-dextran showed increased intestinal permeability in the highest dose, though no morphological differences were found throughout the gastrointestinal tract. Given the lack of other systemic changes, this finding is likely of minimal physiological importance. These results indicate a NOAEL for blueberry polyphenols in OVX-SD rats is ≥ 1000 mg total polyphenols/kg bw/d, which translates to a 70 kg human consuming ~10 g polyphenols. Keywords: Blueberry, Polyphenol, Sub-chronic toxicity. Highlights: Evaluated subchronic oral toxicity of purified blueberry polyphenols in OVX rats. No adverse effects induced by purified blueberry polyphenols in rats. Proposed NOAEL of ≥1000 mg/kg bw/d for blueberry polyphenols in OVX rats. Blueberry polyphenol dietary supplements are likely safe to consume.